Entrepreneurship, innovation, and platforms - Furman, Jeffrey L.; Gawer, Annabelle, 1969-; Silverman, Brian S.; Stern, Scott, 1969- (Advances in strategic management ;, 2017)
Technology-based industries have come to account for ever-greater shares of economic activity during the last 30 years. Recently, rapid, digitally-enabled technological change has generated new opportunities for value creation, enabled new ways of capturing value, and stimulated the emergence of new organizational forms such as platforms and ecosystems. Together with the development of supporting institutions, including incubators, accelerators, and increasingly creative ways of funding new ventures, this has led to an explosion of interest in entrepreneurial activity across industries and sectors. Scholars, policymakers and practitioners recognize the importance of technological innovation and entrepreneurship for competitive advantage, comparative advantage, and society's economic well-being. There is tremendous academic and practical interest not only in how new ventures assemble resources necessary to deliver value, but also on how incumbent organizations may adapt to harness technological innovation, and on how industries evolve in the face of this pervasive technological change. Despite recent advances in our understanding of how innovation and entrepreneurship impact the creation and appropriation of value, numerous questions remain unanswered. This volume draws together scholars working at the forefront of entrepreneurship-, strategy-, and innovation-related domains to explore these questions. The volume makes particular contributions to the entrepreneurship, innovation, and platform literatures.- Resumé vydavatel